IMPACT OF COMMERCIAL AGRICULTURE CREDIT SCHEME ON TECHNICAL EFFICIENCY OF RICE FARMING IN KANO STATE, NIGERIA - GYONG, YERIMA EMMANUEL; DURU, MIKE CHIBUNDU; NJIFORTI, PETER PIDVIGA; ISAH, SALAMATU IDRIS (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2022)
The purpose of this study is to empirically evaluate the effect of commercial agriculture credit scheme on technical efficiency of rice farming in Kano State, Nigeria. Primary data was sourced from 394 beneficiary farmers of commercial agriculture credit scheme (CACS) through survey method in the period 2009–2020. Multi-stage sampling technique was used for the study across the existing agricultural zones. The study employed the stochastic frontier model. The model specified was estimated by likelihood estimates of stochastic frontier production function and inefficiency determinants of rice farming using STATA 14. The findings revealed that before CACS, the regression of the stochastic frontier estimates of technical efficiency revealed that 96.7% had technical efficiency (TE) of 0.75 and above while 3.3% of the farmers operate less than 0.75 efficiency level. After accessing CACS, the regression of the stochastic frontier estimates of technical efficiency level revealed that 92.9% of the farmers had technical efficiency between 0.50 and 0.74, while 7.03% of the farmers operate at less than 0.49 efficiency level. This means that most of the farmers are technically inefficient. The value of the amount borrowed was positive with a value of 0.3453. The implication is that, after accessing CACS, the loan increased the inefficiency of rice farmers. Also the age of farmer and education of farmer led to technical inefficiencies in rice farming. Therefore the result concluded that commercial agriculture credit scheme have led to the technical inefficiency of rice farming in the study area.